Enhanced expression of dltABCD is associated with development of daptomycin nonsusceptibility in a clinical endocarditis isolate of Staphylococcus aureus - Yang, Soo-Jin (2009)
Using isogenic clinical bloodstream Staphylococcus aureus strains from a patient with relapsing endocarditis, we investigated transcriptional profiles of mprF and dlt genes in the context of cell surface charge and daptomycin nonsusceptibility. As in prior studies, a point mutation within mprF was observed in the daptomycin-nonsusceptible strain. However, neither the transcriptional profile of mprF, nor membrane phospholipid analyses were compatible with the anticipated mprF gain-in-function phenotype. In contrast, we demonstrated enhanced dlt expression coincident with increased positive surface charge and reduced daptomycin binding.